2021
DOI: 10.1002/aqc.3533
|View full text |Cite
|
Sign up to set email alerts
|

New contribution on the distribution and ecology of Dendrophyllia ramea (Linnaeus, 1758): abundance hotspots off north‐eastern Sicilian waters

Abstract: Dendrophyllia ramea is a poorly known arborescent scleractinian coral, whose worldwide distribution is limited to the southern part of the Mediterranean basin, and to the Atlantic Ocean between Macaronesia and Gulf of Cadiz. The geographical distribution and abundance of D. ramea were herein updated, considering a total of 19 records, seven of which have never previously been reported in scientific papers. Between 2010 and 2017, five Remotely Operative Vehicle surveys carried out along the Sicilian coast recor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 22 publications
2
8
0
Order By: Relevance
“…Smaller colonies formed patches at higher densities. These results are comparable with those recently obtained by Orejas et al (2017), while they are higher than those reported by Salvati et al (2021) for northern Sicily.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Smaller colonies formed patches at higher densities. These results are comparable with those recently obtained by Orejas et al (2017), while they are higher than those reported by Salvati et al (2021) for northern Sicily.…”
Section: Discussionsupporting
confidence: 91%
“…In the study area, this species thrives on boulders on a sedimentary plateau at 70-80 m depth, as described by several authors in other Mediterranean areas (Zibrowius, 1980;Aguilar et al, 2006;Templado et al, 2009). Moreover, the bathymetric range is similar to that observed by Salvati et al (2021) in northern Sicily. Some isolated D. ramea corallites were also observed on the soft substratum (Figure 3D) between boulders.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations